A new species of Chiasmocleis (Anura: Microhylidae) from the Iquitos region, Amazonian Peru, with possible direct development - Moravec, Jiří; Köhler, Jörn (Zootaxa, 2007)
We describe a new species of microhylid frog of the genus Chiasmocleis from the upper Amazon basin of Peru (area of Iquitos, Departamento Loreto). The new species is characterized by small size, distinct reduction of fingers I and IV and the presence of large unpigmented eggs in the oviducts. The latter character is so far unknown in the recognized species of the genus and may indicate the presence of a terrestrial reproductive mode. The generic placement of the new species is discussed.